What's in the water? - Target and suspect screening of contaminants of emerging concern in raw water and drinking water from Europe and Asia - Tröger, Rikard; Ren, Hanwei; Yin, Daqiang; Postigo, Cristina; Nguyen, Phuoc Dan; Baduel, Christine; Golovko, Oksana; Been, Frederic; Joerss, Hanna; Boleda, Maria Rosa; Polesello, Stefano; Roncoroni, Marco; et al. (Water research, 2021)
There is growing worry that drinking water can be affected by contaminants of emerging concern (CECs), potentially threatening human health. In this study, a wide range of CECs (n = 177), including pharmaceuticals, pesticides, perfluoroalkyl substances (PFASs) and other compounds, were analysed in raw water and in drinking water collected from drinking water treatment plants (DWTPs) in Europe and Asia (n = 13). The impact of human activities was reflected in large numbers of compounds detected (n = 115) and high variation in concentrations in the raw water (range 15-7995 ng L-1 for ∑177CECs). The variation was less pronounced in drinking water, with total concentration ranging from 35 to 919 ng L-1. Treatment efficiency was on average 65 ± 28%, with wide variation between different DWTPs. The DWTP with the highest ∑CEC concentrations in raw water had the most efficient treatment procedure (average treatment efficiency 89%), whereas the DWTP with the lowest ∑177CEC concentration in the raw water had the lowest average treatment efficiency (2.3%). Suspect screening was performed for 500 compounds ranked high as chemicals of concern for drinking water, using a prioritisation tool (SusTool). Overall, 208 features of interest were discovered and three were confirmed with reference standards. There was co-variation between removal efficiency in DWTPs for the target compounds and the suspected features detected using suspect screening, implying that removal of known contaminants can be used to predict overall removal of potential CECs for drinking water production. Our results can be of high value for DWTPs around the globe in their planning for future treatment strategies to meet the increasing concern about human exposure to unknown CECs present in their drinking water.
Keywords: monitorování životního prostředí; Drinking water; Europe; Removal efficiency; lidé; Asie; Evropa; Environmental Monitoring; chemické látky znečišťující vodu; Drinking Water; Contaminants of emerging concern; Water Pollutants, Chemical; Water Purification; High-resolution mass spectrometry; Humans; Suspect screening; Asia; Water treatment; čištění vody; pitná voda